Observation of associated production of a Z boson with a D meson in the forward region - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; De Cian, Michel; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Gersabeck, Evelina; Grillo, Lucia; Grünberg, Oliver; Hansmann-Menzemer, Stephanie; Hartmann, Thomas; et al. (Journal of high energy physics, 2014)
A search for associated production of a Z boson with an open charm meson is presented using a data sample, corresponding to an integrated luminosity of 1.0 fb−1 of proton-proton collisions at a centre-of-mass energy of 7TeV, collected by the LHCb experiment. Seven candidate events for associated production of a Z boson with a D0 meson and four candidate events for a Z boson with a D+ meson are observed with a combined significance of 5.1 standard deviations.
The LHCb collaboration: R. Aaij, B. Adeva, M. Adinolfi, A. Affolder Z. Ajaltouni, J. Albrecht, F. Alessio, M. Alexander, S. Ali, G. Alkhazov [und 666 weitere]
Gesehen am 19.08.2020